The development of two-variable function derivative learning using Geogebra - Hedi, Hedi; Mulyadi, Ahmad Deni; Suryani, Anny; Binarto, Agus; Agoes, Farida (SAINTIS Publishing, 2023)
Mathematics learning model using GeoGebra software has become a handy tool in teaching mathematical concepts and applications. Students can conduct experiments and explore mathematical concepts in an interactive and fun way with GeoGebra software. Using GeoGebra in learning mathematics of two-variable functions can increase students' understanding on the topic discussed, strengthen mathematical computational and visualization skills, and motivate them to know more and better complex mathematical concepts. From this perspective, this study aims to know the impact of using GeoGebra on students' understanding of the derivative of a function of two variables. Furthermore, this study was conducted on two groups of students, namely the control group (not using GeoGebra) of 53 students and the experimental group (using GeoGebra) consisting of 50 students. Based on these results descriptively students in the experimental group have higher scores on the assessment of skills in determining partial derivatives and their application. Statistically, there is a difference between the experimental and control groups in understanding the function of the derivative of the two variables.